The effect of unrealistic optimism in the intention of the use of the condom as method of prevention of non-wanted pregnancies and sexually transmitted diseases - Pons Salvador, Gemma; Miralles Díaz, María Teresa; Guillén Salazar, Federico (Anales de Psicología / Annals of Psychology, 2010)
Unrealistic optimism (UO) occurs when a person considers that his or her probability to go through an unpleasant or dangerous event is lower than that in others. It is a cognitive bias that can endanger the effec-tiveness of health care programmes. This article explores the existence of UO related to the use of the condom in situations of non-wanted preg-nancies (NWP) and sexually transmitted diseases (STD). We have used a modified version of the questionnaire designed by Zakay (1996) and later adjusted by Fernández-Castro, Limonero, Rovira y Albaina (2002) (2002) in a sample of 292 college students with more than 20 years old (181 women and 111 men). Our results confirm the existence of the UO in the use of the condom, finding a greater bias in NWP’s situations than in STD. Specifically, we found that study subjects believed they were less liable to go through a NWP if not using the condom (or if it tore) than other people. Regarding STD, they also believed that their probability of being infected without using the condom was lower than in others. There-fore, we found that men are more prone to UO than women.